Do Not Love Your Neighbour as Yourself? : The Role of Neighbourly Love in Law, Theology of Law, and Church Polity - Broeke, Leon van den, (Brill Research Perspectives in International Law., 2025)
This book explores the notion of neighbourly law. In the twentieth century, some German church law scholars viewed neighbour law as the foundational principle of the church law system. However, this perspective has since evolved. Around the year 2000, there was a growing focus in the Anglo-Saxon world on the relationship between love and law. Although neighbour law can no longer be regarded as the sole foundation of church law, the obligation remains to reflect critically on the role of the neighbour in legal theological discourse, the development and codification of church law, and its practical application. Canon law is a diaconal ordering of God's love, or neighbour law.